Rehabilitasi NAPZA Metode Terapi Komunitas untuk Perbaikan Psikopatologi, Citra Diri dan Kualitas Hidup - Firdaus Yamani; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem of substance abuse has made all countries in the world worried. The United Nations Office on Drugs and Crime noted that at least 271 million people worldwide or 5.5% had consumed substances in 2017. The dangers of substance abuse in users have an impact on biological, psychological and social aspects. These various adverse impacts will certainly have an impact on psychological conditions and a decrease in self-esteem, which in turn can lead to a decrease in quality of life. Community therapy is a treatment that uses a psychosocial approach, a community of addicts who help each other to recover and keep quitting substances. Implementation of drug rehabilitation with community therapy methods can improve psychopathology, self-image and quality of life.